Answer:
4m and ms are peanut
Step-by-step explanation:
9+2=11 and theres 15 total so 15-11= 4
Answer:
-0.5,-2/5,0,0.67,7/9
Step-by-step explanation:
Well since the bigger the negative the lesser the number it is itself so -0.5 is the least. The fraction -2/5 turn It into a decimal and you’ll get -0.4 which is greater then -0.5. Then the next number is 0 which is greater then any negative number. Then its 0.67 becuase the other positive fraction Is 0.78 simplified.
Multiply .6 x 132 and that gets you 79.2 then you add 132 +79.2 =$211.20
Answer: $0.66
Step-by-step explanation: Just divide 3 / $1.98 and you will get $0.66.
Fairly simple, But the only thing I don't understand is why a melon is on sale for $0.66. Thats CHEAP! Give me 100 :)
Answer:
The solution is (3,13) and (-1,-3). So none of the mentioned options is correct.
Step-by-step explanation:
Given that
![y = 4x + 1 (i)](https://tex.z-dn.net/?f=y%20%3D%204x%20%2B%201%20%20%28i%29)
![y = x^2 + 2x -2 (ii)](https://tex.z-dn.net/?f=y%20%3D%20x%5E2%20%2B%202x%20-2%20%28ii%29)
Now, by susbstituting the value of 'y' from equation i to equation ii, we get
![4x+1=x^2 + 2x -2](https://tex.z-dn.net/?f=4x%2B1%3Dx%5E2%20%2B%202x%20-2)
![0=x^2 + 2x -2-4x-1](https://tex.z-dn.net/?f=0%3Dx%5E2%20%2B%202x%20-2-4x-1)
![0=x^2 + (2x -4x) +(-2-1)](https://tex.z-dn.net/?f=0%3Dx%5E2%20%2B%20%282x%20-4x%29%20%2B%28-2-1%29)
![0=x^2 + (-2x) +(-3)](https://tex.z-dn.net/?f=0%3Dx%5E2%20%2B%20%28-2x%29%20%2B%28-3%29)
![0=x^2 -2x -3](https://tex.z-dn.net/?f=0%3Dx%5E2%20-2x%20-3)
![x^2 -2x -3 = 0 (iii)](https://tex.z-dn.net/?f=x%5E2%20-2x%20-3%20%3D%200%20%28iii%29)
Now by factorization, equation iii can be written as
![x^2 -3x +x -3 = 0](https://tex.z-dn.net/?f=x%5E2%20-3x%20%2Bx%20-3%20%3D%200)
![x(x -3) + 1(x -3) = 0](https://tex.z-dn.net/?f=x%28x%20-3%29%20%2B%201%28x%20-3%29%20%3D%200)
![(x -3)(x +1) = 0](https://tex.z-dn.net/?f=%28x%20-3%29%28x%20%2B1%29%20%3D%200)
x = 3 and x = -1
By putting the values of x in equation i, we get
y = 4(3) + 1
y = 12 +1
y = 13
and
y = 4(-1) + 1
y = -4 +1
y = -3
Therefore, the solution is (3,13) and (-1,-3). So none of the mentioned options is correct.